Peran Koperasi Mahasiswa dalam Meningkatkan Kesejahteraan Anggota dan Implikasinya Terhadap Ketahanan Ekonomi Anggota (Studi Pada Kopma UIN Sunan Kalijaga Yogyakarta) - Mohamad Zaim (Institut Agama Islam Negeri Kendari, 2018)
This study examined the role of student cooperatives in improving member welfare and its implications on the economic resilience of members, by taking the object of research in Student Cooperation UIN Sunan Kalijaga Yogyakarta. The purpose of this study was to analyze the role of Student Cooperative